THE ROLE OF MARKETING STRATEGIES IN INCREASING COMPETITIVENESS (A STUDY AT PT MACAKAL PANGAN SEJAHTERA CIAMIS) - Ipik Permana; Wiwin Setianingsih; Elis Badriah; Purnama Sari; Lia Yulia; Andre Herdiansyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The industrial era is characterized by the dominant use of electronic media, as is the case in the world of marketing where the use of electronic media has become increasingly massive. The superiority of a company is seen from the development of the company's ability to create superior value by utilizing the resources it has. Problems faced in study This covers How strategy marketing, competitiveness and the role of marketing strategy at PT. Macakal Pangan Sejahtera. Objective study This is known And analyze Strategy marketing , Power competitive and Role strategy marketing in effort increase Power competition PT. Macakal Pangan Sejahtera. Method used in study This is method study qualitative descriptive. Results Study show Strategy marketing carried out by PT. Macakal Pangan Sejahterain a way general Already Walk Enough Good. Strategy marketing Already quite optimal, with promotion indicators that play the most role. Insufficient indicators is place indicator. Power competitive at PT. Macakal Pangan Sejahtera Already Enough Good in accordance with indicators that have been set that is quality product, price competitive and uniqueness. Price competitive become the most important indicator. Insufficient indicators is indicator uniqueness product. With so can concluded that role strategy marketing own role important in increase Power competitive so that PT Macakal Ciamis Pangan Sejahera capable compete in a way competitive and superior between its competitors. Keywords : Marketing, Strategy Marketing, Power Competition, Competitors, Macakal Ciamis